(untitled) (Bulletin of criminological association of Ukraine, 2024)
The article emphasizes that in the conditions of martial law, the activities of the police in the direction of ensuring the national security of the state underwent a radical rethinking. This rethinking is based on previous processes of reforming domestic law enforcement agencies, in particular during European and Euro- Atlantic integration. It is noted that the vector for European integration announced in previous years from the first days of the introduction of the legal regime of martial law ensured the stability and coherence of the activities of police bodies and units in the course of providing a wide range of services to help the population and identify threats to national security, in particular in terms of countering collaborative activities, and also contributed to maximum active support from European partners. Attention is focused on the fact that the activities of the police in ensuring the national security of the state are reduced to documenting the consequences of war crimes, investigating the facts of collaborative activities, participating in the liquidation of the consequences of emergency situations, including enemy artillery and missile attacks, as well as ensuring the deterrence of armed aggression against Ukraine in in the course of direct participation in combat operations of police rifle brigades, protection of the state’s airspace during the destruction of enemy unmanned aerial vehicles, strengthening of the protection of the state border of Ukraine by units formed from students and employees of higher education institutions with specific training conditions that train police officers, etc. It is argued that granting the police a wide range of powers in the field of ensuring national security and repelling armed aggression should be an exclusively temporary, forced step and not lead to the gradual militarization of domestic law enforcement agencies, which threatens the implementation of democratic civilian control over their activities and ensuring compliance in their daily activities human rights It is noted that in the conditions of martial law, the police also perform a number of tasks in the course of ensuring the financial and informational component of the state’s national security.